2007
DOI: 10.1073/pnas.0608409104
|View full text |Cite
|
Sign up to set email alerts
|

Tradeoffs between income, biodiversity, and ecosystem functioning during tropical rainforest conversion and agroforestry intensification

Abstract: Losses of biodiversity and ecosystem functioning due to rainforest destruction and agricultural intensification are prime concerns for science and society alike. Potentially, ecosystems show nonlinear responses to land-use intensification that would open management options with limited ecological losses but satisfying economic gains. However, multidisciplinary studies to quantify ecological losses and socioeconomic tradeoffs under different management options are rare. Here, we evaluate opposing land use strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
316
1
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 437 publications
(340 citation statements)
references
References 41 publications
(72 reference statements)
13
316
1
10
Order By: Relevance
“…Ces études sont unanimes sur le fait que les systèmes agroforestiers à base de cacaoyers abritent de nombreuses espèces par rapport aux plantations monoculturales. D'autres études ont aussi permis de démontrer leur importance dans la séquestration du carbone atmosphérique (Stephan-Dewenter et al, 2007;Smiley et Kroschel, 2008 ;Duguma et al, 2001 ;KottoSame et al, 1997 ;Gockowski et Sonwa, 2011 ;Somarriba et al, 2013).…”
Section: Introductionunclassified
“…Ces études sont unanimes sur le fait que les systèmes agroforestiers à base de cacaoyers abritent de nombreuses espèces par rapport aux plantations monoculturales. D'autres études ont aussi permis de démontrer leur importance dans la séquestration du carbone atmosphérique (Stephan-Dewenter et al, 2007;Smiley et Kroschel, 2008 ;Duguma et al, 2001 ;KottoSame et al, 1997 ;Gockowski et Sonwa, 2011 ;Somarriba et al, 2013).…”
Section: Introductionunclassified
“…Forests yield multiple benefits and products: among them fodder, firewood, timber, and many non-timber products (21,22). Multiple stakeholders advance competing claims to such benefits from forest commons (23).…”
mentioning
confidence: 99%
“…However, research has shown that poorly planned intensification actually exacerbates vulnerability to climate change (Lin et al 2008) and can lead to permanent deforestation with severe consequences for ecosystem services and soil fertility (van Vliet et al 2012). Under the alternative approach of agroforestry intensification, agricultural intensification occurs in association with trees, with the objective of conserving ecosystem services and increasing farmers' income (Steffan-Dewenter et al 2007). …”
Section: Scenario With Adaptation and Sustainable Managementmentioning
confidence: 99%